Localized proteomic differences in the choroid plexus of Alzheimer's disease and epilepsy patients - Leitner, Dominique F.; Kanshin, Evgeny; Faustin, Arline; Thierry, Manon; Friedman, Daniel; Devore, Sasha; Ueberheide, Beatrix; Devinsky, Orrin; Wisniewski, Thomas (Frontiers in Neurology, 2023)
Introduction: Alzheimer’s disease (AD) and epilepsy are reciprocally related. Among sporadic AD patients, seizures occur in 10-22% and subclinical epileptiform abnormalities occur in 22-54%. Cognitive deficits, especially short-term memory impairments, occur in most epilepsy patients. Common neurophysiological and molecular mechanisms occur in AD and epilepsy. The choroid plexus undergoes pathological changes in aging, AD, and epilepsy, including decreased CSF turnover, amyloid beta (Aβ) and tau accumulation due to impaired clearance, and disrupted CSF amino acid homeostasis. This pathology may contribute to synaptic dysfunction in AD and epilepsy. Methods: We evaluated control (n=8), severe AD (n=8; A3, B3, C3 neuropathology), and epilepsy autopsy cases (n=12) using laser capture microdissection (LCM) followed by label-free quantitative mass spectrometry on choroid plexus adjacent to the hippocampus at the lateral geniculate nucleus level. Results: Proteomics identified 2459 proteins in the choroid plexus. At a 5% false discovery rate (FDR), 616 proteins were differentially expressed in AD vs. control, 1 protein in epilepsy vs. control, and 438 proteins in AD vs. epilepsy. There was more variability in the epilepsy group across syndromes. Top signaling pathways with differentially expressed proteins in AD vs. control included cell metabolism; activated fatty acid beta-oxidation (p=2.00 x 10-7, z = 3.00), inhibited glycolysis (p=1.00 x 10-12, z = -3.46). For AD vs. epilepsy, altered pathways included cell metabolism pathways, activated complement system (p=5.62 x 10-5, z = 2.00), and pathogen induced cytokine storm (p=2.19 x 10-2, z = 3.61). Of the 617 altered proteins in AD and epilepsy vs. controls, 497 (81%) were positively correlated (p<0.001, R2 = 0.27). Discussion: We found altered signaling pathways in the choroid plexus of severe AD cases and many correlated changes in protein expression of cell metabolism pathways in AD and epilepsy cases. Shared molecular mechanisms should be investigated further to distinguish primary pathogenic from secondary changes. This could inform novel therapeutic strategies to prevent disease progression or restore normal function. A focus on dual diagnosed AD/epilepsy cases, specific epilepsy syndromes like temporal lobe epilepsy, and changes across different severity levels in AD and epilepsy would add to our understanding.